Contribution of Autonomic Reflexes to the Hyperadrenergic State in Heart Failure - Toschi-Dias, Edgar; Rondon, Maria Urbana P. B.; Cogliati, Chiara; Paolocci, Nazareno; Tobaldini, Eleonora; Montano, Nicola (Frontiers in Neuroscience, 2017)
Heart failure (HF) is a complex syndrome representing the clinical endpoint of many cardiovascular diseases of different etiology. Given its prevalence, incidence and social impact, a better understanding of HF pathophysiology is paramount to implement more effective anti-HF therapies. Based on left ventricle (LV) performance, HF is currently classified as follows: (1) with reduced ejection fraction (HFrEF); (2) with mid-range EF (HFmrEF); and (3) with preserved EF (HFpEF). A central tenet of HFrEF pathophysiology is adrenergic hyperactivity, featuring increased sympathetic nerve discharge and a progressive loss of rhythmical sympathetic oscillations. The role of reflex mechanisms in sustaining adrenergic abnormalities during HFrEF is increasingly well appreciated and delineated. However, the same cannot be said for patients affected by HFpEF or HFmrEF, whom also present with autonomic dysfunction. Neural mechanisms of cardiovascular regulation act as “controller units”, detecting and adjusting for changes in arterial blood pressure, blood volume, and arterial concentrations of oxygen, carbon dioxide and pH, as well as for humoral factors eventually released after myocardial (or other tissue) ischemia. They do so on a beat-to-beat basis. The central dynamic integration of all these afferent signals ensures homeostasis, at rest and during states of physiological or pathophysiological stress. Thus, the net result of information gathered by each controller unit is transmitted by the autonomic branch using two different codes: intensity and rhythm of sympathetic discharges. The main scope of the present article is to i) review the key neural mechanisms involved in cardiovascular regulation; ii) discuss how their dysfunction accounts for the hyperadrenergic state present in certain forms of HF; and iii) summarize how sympathetic efferent traffic reveal central integration among autonomic mechanisms under physiological and pathological conditions, with a special emphasis on pathophysiological characteristics of HF.